CONFERENCES AND SYMPOSIA : Light bullet dynamics in uniform dielectrics (50th anniversary of the Institute of Spectroscopy, Russian Academy of Sciences). (28th May 2019) - Chekalin, S V; Kompanets, V O; Dormidonov, A E; Kandidov, V P
Abstract: Experiments and numerical simulations performed jointly by the Institute of Spectroscopy, Russian Academy of Sciences, and Lomonosov Moscow State University have shown that unlike solitons in guiding structures, the light bullet, a wave packet compressed to the extreme in space and time in the bulk of a transparent dielectric, is a short-lived formation whose free path is no more than several hundred micrometers. The supercontinuum spectrum generated by a light bullet experiences superbroadening, and an isolated anti-Stokes wing emerges if the bullet is compressed to the state of a wave packet close to the single-cycle one, and a plasma channel develops. These findings have been confirmed by numerical simulations and experiments demonstrating periodic density modulation of the color centers induced in LiF, which occurs due to the difference between the wave packet envelope and frequency-carrier velocities in a medium.